Struktur Komunitas Diatom di Perairan Pantai Cemara Kabupaten Lombok Barat sebagai Dasar Penyusunan Modul Sistematika Cryptogamae - Nurbaya, Tresia Siti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The waters of Cemara Beach, Lembar District, West Lombok Regency, have extraordinary marine potential. One of Indonesia's marine biodiversity is Diatom microalgae. The aims of this study were: 1) to find out the types of Diatoms in Cemara Beach, West Lombok Regency; 2) to determine the level of Diatom abundance in Cemara Beach, West Lombok Regency; 3) to determine the diversity index of Diatoms in Cemara Beach, West Lombok Regency; 4) to determine the evenness of Diatoms in Cemara Beach, West Lombok Regency; 5) to determine the species population that dominates the Diatom community in Cemara Beach, West Lombok Regency; and 6) to determine the validity of the Cryptogamae systematics module developed based on research results. This type of research is descriptive research and development research using the 4D model from Thiagarajan which is modified into 3D. Descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena, while development research is research consisting of define, design, and develop. From the results of the study it can be seen that there are 12 species of Diatoms found, namely Diatoma Hyalina kutzing numbering 6, Chaetoceros didinum Enhenberg varanglica numbering 3, Chaetoceros subsecundum Hustedt numbering 18, Chaetoceros pendulum Karsten numbering 2, Chaetoceros compressum Lauder numbering 37, Skeletonema costatum Cleve totaling 20 , Pseudo nitzhia seriata numbered 7, Nitzhia pungen numbered 4, Thalassionema nitzchiodes Grunov numbered 40, Biddulphia mobiliensis Bailey numbered 1, Hemiaulus sinensis Greville numbered 20, Euchampia comuta Grunow numbered 7. In the data on the abundance of Diatom species at station I there were 65 species, station II totaling 45 species, and station III totaling 55 species. In the analysis of the diversity index, the number of species at station I was 0.967 species, station II was 0.965, station III was 0.998 species, in the evenness analysis the number of species at station I was 0.998, station II was 0.335, station III was 0.998 species, while in the dominance analysis Diatoms The number of Diatoms at station I was 26.5063, station II was 24.2886, and station III was 15.2543. While the development research obtained the results from the validators: content/material expert on average 4, linguist on average 3.9, and display expert on average 4.3 with a good category and no need for revision. So it can be concluded that the module is feasible to use.